The Impact of Exceptional Circumstances on Procedural Deadlines before Civil Courts - Ali Mahmoud Abu Maria,; Aseel Talat Sulaiman,; Iman Rifat Tahboub,; Jibreel Mutasim Darawsha,; Hamza Diyab Shashtari,; Hamza Hisham Abu-Beeh,; Mays Khalil Maqboul, (International Journal of Law Research and Studies, 2026)
This study aims to clarify the impact of the doctrine of Exceptional Circum-stances on procedural deadlines in Palestinian legislation. This study's significance stems from its emphasis on a matter that is fundamental to civil litigation, encompassing all aspects and components of a lawsuit.  The investigation revealed the issue of the lack of an explicit provision in Palestinian legislation that regulates the doctrine. Thus, the question arises: Did the Palestinian legislator succeed in issuing the temporary decree-law No. (10) Of 2020 concerning the suspension of procedural deadlines? To answer this research problem, the descriptive-analytical method was adopted by examining the le-gal provisions governing the subject, particularly those found in the Civil and Commercial Procedure Law No. 2 of 2001 and Decree-Law No. (10) Of 2020. The study concludes that the Civil and Commercial Procedure Law lacks specific regulations for cases meeting the criteria of exceptional circumstances and their impact on procedural deadlines and legal time limits. Moreover, the existing regulations concerning the suspension and interruption of deadlines in the Civil and Commercial Procedure Law are not applicable to these circumstances. The study advocates for the modification of the Civil and Commercial Procedure Law to include a provision that governs the suspension of procedural deadlines in extraordinary circumstances, in-stead of depending exclusively on temporary legislation or general rules that necessitate interpretation and legal adjustment for application to specific exceptional events.Penelitian ini bertujuan untuk menjelaskan dampak doktrin keadaan luar biasa (Exceptional Circumstances) terhadap batas waktu prosedural dalam perundang-undangan Palestina. Signifikansi penelitian ini terletak pada penekanannya terhadap isu yang mendasar dalam litigasi perdata, yang mencakup seluruh aspek dan unsur dari suatu gugatan.Penelitian ini mengungkapkan adanya kekosongan pengaturan eksplisit dalam perundang-undangan Palestina yang secara khusus mengatur doktrin tersebut. Oleh karena itu, muncul pertanyaan: Apakah legislator Palestina berhasil dalam menerbitkan dekrit undang-undang sementara No. (10) Tahun 2020 yang berkaitan dengan penangguhan batas waktu prosedural?Untuk menjawab permasalahan penelitian ini, digunakan metode deskriptif-analitis dengan menelaah ketentuan hukum yang mengatur topik ini, khususnya yang terdapat dalam Undang-Undang Prosedur Perdata dan Komersial No. 2 Tahun 2001 serta Dekrit Undang-Undang No. (10) Tahun 2020.Penelitian ini menyimpulkan bahwa Undang-Undang Prosedur Perdata dan Komersial tidak memiliki ketentuan khusus yang mengatur kasus-kasus yang memenuhi kriteria keadaan luar biasa serta dampaknya terhadap batas waktu prosedural dan tenggat hukum. Selain itu, ketentuan yang ada terkait dengan penangguhan dan penghentian batas waktu dalam undang-undang tersebut tidak dapat diterapkan pada kondisi semacam ini.Penelitian ini merekomendasikan agar Undang-Undang Prosedur Perdata dan Komersial direvisi untuk memasukkan ketentuan yang mengatur penangguhan batas waktu prosedural dalam keadaan luar biasa, sehingga tidak semata-mata bergantung pada peraturan sementara atau ketentuan umum yang memerlukan penafsiran dan penyesuaian hukum untuk dapat diterapkan pada peristiwa luar biasa tertentu.
Keywords: Exceptional Circumstances; Force Majeure; COVID-19 Pandemic; Procedural Deadlines; Suspension of Time Limits